Peninsular southern Europe refugia during the Middle Palaeolithic: an introduction - Bicho, Nuno (2022)
Neanderthals faced great environmental and climatic instability during the Pleistocene, which may have influenced their lithic technology, subsistence patterns, mobility, behaviour and survival. Modern research assessing the effect of climate and environment on the Middle Palaeolithic and transition to the Upper Palaeolithic has often turned to southern Europe, specifically peninsular southern Europe (Iberia, Italy and the Balkans). These are regions typically regarded as refugia during periods of unfavourable climatic conditions, inspiring hundreds of palaeoenvironmental studies at Neanderthal sites and hypotheses on late Neanderthal survival in locations with relative ameliorated conditions. Here, we present the topic of the special issue focusing on peninsular southern Europe refugia during the Middle Palaeolithic covering the three main peninsulas. Its 16 contributions discuss relevant data on peninsular southern Europe as possible refugia during periods of unfavourable climate during the Middle Palaeolithic and transition to Upper Palaeolithic.